Topical corticosteroid concerns from the clinicians' perspective. (4th July 2017) - Mueller, Simon M.; Tomaschett, Dominique; Vogt, Deborah R.; Itin, Peter; Cozzio, Antonio; Surber, Christian
Abstract: Purpose: Topical corticosteroids concerns (TCC) are common in dermatology patients, possibly leading to non-adherence to topical corticosteroids (TCS) and poor disease control. Clinicians play a key role in that context, as they can reduce or reinforce these concerns. It is unknown, if clinicians have accurate knowledge of TCC to appropriately address this issue and whether they have concerns themselves to use TCS. This questionnaire-based study aimed to assess these two aspects. Materials and methods: Accuracy of knowledge was defined by how close the clinicians' estimates were to reference values of our previous study, in which we had examined TCC in dermatology outpatients. Moreover, clinicians indicated whether they have concerns themselves to use TCS. Results: Totally 202 clinicians participated. They underestimated both the prevalence of TCC and the resulting non-adherence. Whereas most clinicians correctly estimated characteristics of patients with TCC and the impact of patient information, only 31% of clinicians knew that skin atrophy was the leading concern, and only 30% correctly ranked the reasons for TCC. 74% of the clinicians had at least minor concerns themselves. Conclusion: The majority of clinicians may have inaccurate knowledge of certain aspects of TCC and own concerns to use TCS.